Creating a place for ourselves : lesbian, gay, and bisexual community histories - Beemyn, Genny, 1966- (Routledge, 1997)
Creating a Place For Ourselves offers an historical look at gay life in the United States before the gay liberation movement. Examining not only the large gay communities of New York, San Francisco, and Fire Island, but also the thriving gay populations in cities like Detroit, Buffalo, Washington, Birmingham, and Flint, the contributors assembled here demonstrate that gay communities are truly everywhere.